PELAKSANAAN RESTRUKTURISASI KREDIT MACET BERDASARKAN PERATURAN BANK INDONESIA DAN HAMBATANNYA PADA PT BANK RAKYAT INDONESIA CABANG BINJAI - Novrilanimisy Novrilanimisy; Tan Kamello; Sunarmi Sunarmi; Dedi Harianto (Universitas Sumatera Utara, 2014)
ABSTRACT Bank Indonesia through the Regulation of Bank Indonesia No. 14/15/PBI/2012 on the Assessment on the Asset Quality of Commercial Bank. Credit restructuring is an attempt of a Bank to handle debtors who get difficulty in paying off their debts by decreasing interest rate, extending credit term, reducing the arrears of bank interest, reducing bank main arrears, increasing credit facility, and/or conversing credit to temporary equity. Bank Rakyat Indonesia also issued guidelines for handling credit through credit restructuring,based on the Circulation Letter of PT Bank Rakyat Indonesia No. S.12-DIR/ADK/5/2013. The parameter for determining non-performing credit which is worthy of getting restructuring is the debtors who get difficulty in paying off principal or credit interest and they should have good business prospect and are able to pay off their debt after it has been restructured. Some obstacles faced by Bank Rakyat Indonesia Cabang Binjai are as follows: debtors are difficult to cooperate, debtors are not transparent in conducting negotiation, Bank gets difficulty in approaching debtors since they are not cooperative, the content of the restructuring is not complied according to what has been agreed, credit restructuring is not supported by the information about the complete document about debtors’ businesses, and Bank finds it difficult to directly control debtors’ businesses. Keywords : Credit restructuring, Bank, non-performing credit